Current sharing strategies in DC microgrids - Lee, Joel Wei Bin (Nanyang Technological University, 2024)
With the increasing use of renewable energy comes additional challenges. This includes managing distributed generation, the intermittency of many renewable sources and the complexity of implementing energy storage systems. A promising approach to address these challenges is through DC microgrids. DC Microgrids have increased reliability, greater efficiency between DC sources and loads, and simpler control than conventional AC grids. The objective of this project was to design a control system for a DC microgrid and assess different current sharing strategies. This was done by designing the primary controller, implementing it in a simple DC microgrid, followed by testing of several secondary control strategies, inside PLECS software. The secondary control strategies included droop control, centralized voltage restoration, distributed voltage restoration and adaptive virtual resistance. Each approach was assessed based on its voltage regulation to meet desired voltage reference, current sharing to distribute load among sources according to power rating, response time, and stability of the system. The results showed that a combination of adaptive virtual resistance and distributed voltage restoration was able to achieve ideal current sharing and voltage regulation. Implementing adaptive virtual resistance alone could achieve ideal current sharing with only a small detriment to voltage regulation and was also a viable approach. Hence, both control strategies are recommended for use in DC microgrids. A choice can be made between the two, by weighing the small improvement in performance against the increased complexity.